Lithium ion battery
By controlling the type and content of additives in the electrolyte, the charging cutoff voltage and CB value in the lithium-ion battery, the problem of difficulty in maintaining long cycle performance while improving the energy density of lithium-ion batteries is solved, and the high energy density and excellent cycle performance are achieved.
Patent Information
- Application Number
- CN202411804332.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
While increasing the energy density of existing lithium-ion batteries, it is difficult to maintain long cycle performance, mainly due to the increase in the positive electrode oxidation potential, the electrolyte decomposition, transition metal dissolution and SEI film destruction and recombination problems.
By controlling the type and content of additives in the electrolyte, the charging cutoff voltage and CB value, the stability of the electrolyte and the stability of the SEI film on the negative electrode surface are ensured, thereby avoiding transition metal ion dissolution and SEI film destruction.
The lithium-ion battery maintains excellent cycling performance while maintaining high energy density, avoiding the problems of electrolyte decomposition and SEI membrane damage.
Smart Images

Figure CN119725736A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium-ion battery. Background Art
[0002] Batteries with high energy density can provide longer working time and driving range at a certain quality, which is especially important for application areas with high requirements for battery energy density.
[0003] At present, in order to improve the energy density of power batteries, the charging cut-off voltage can be appropriately expanded to help the positive electrode to exert a higher gram capacity. At this time, the CB value of the lithium battery is generally adjusted to increase to avoid lithium plating at the negative electrode; however, the increase in the CB value of the lithium battery will cause the positive electrode oxidation potential to become higher, and the electrolyte will undergo oxidative decomposition at high potential, resulting in deterioration of the cycle performance of the lithium battery. In addition, the increase in the charging cut-off voltage will cause the positive electrode transition metal (Fe&Mn) to dissolve. The transition metal exists in the form of ions, causing the ethylene carbonate EC in the electrolyte to be reduced and decomposed, and reduced to a metallic state at the negative electrode, continuously destroying the SEI film on the negative electrode surface, which will further deteriorate the cycle performance of the lithium battery. Summary of the invention
[0004] In order to enable a lithium-ion battery to have both high energy density and long cycle performance, the present application provides a lithium-ion battery.
[0005] The present application provides a lithium-ion battery, which adopts the following technical solution:
[0006] A lithium ion battery, comprising an electrolyte, wherein the electrolyte comprises a solvent, a lithium salt and an additive, and the proportion of the additive in the electrolyte is denoted as A dd , A dd The unit is part, and the charging cut-off voltage of the lithium battery is recorded as V ol , V ol The unit is V;
[0007] The CB value of the lithium battery is related to the A dd , the V ol satisfy The CB value of the lithium battery is a dimensionless value;
[0008] Among them, the additives include negative electrode film-forming additives, positive electrode complexing additives, and positive electrode high-voltage resistant additives.
[0009] The CB value is the designed CB value, which is the ratio of the reversible capacity of the negative electrode sheet per unit area of the battery to the reversible capacity of the positive electrode sheet per unit area of the battery.
[0010] In the present application, the type of additive in the electrolyte and the weight of the additive per hundred parts of the electrolyte are controlled.dd , Lithium battery charging cut-off voltage V ol When the CB value of the lithium battery meets the above conditions, it can avoid the metal ions at the positive electrode from being reduced at the negative electrode, and ensure the complexation of transition metal ions at the positive electrode as much as possible, thereby improving the stability of the electrolyte and the stability of the SEI film at the negative electrode surface. At this time, the content of additives in the electrolyte can also be controlled within an appropriate range, which can not only avoid the destruction and recombination of the SEI film caused by the dissolution of transition metal ions, but also avoid the problem of electrolyte decomposition caused by the increase in the CB value of the lithium battery, which helps to make the lithium battery have a high energy density while maintaining relatively excellent cycle performance.
[0011] when That is, the charging cut-off voltage and CB value of the lithium battery are too low or the proportion of additives in the electrolyte is too high. At this time, the energy density of the lithium battery cannot be effectively exerted, and during the cycle of the lithium battery, lithium deposition is prone to occur on the negative electrode surface. In addition, too high a proportion of additives in the electrolyte will also affect the film formation on the negative electrode surface, which is not conducive to improving the cycle performance of the lithium battery.
[0012] when That is, the charging cut-off voltage and CB value of the lithium battery are too high or the proportion of additives in the electrolyte is too low. At this time, the electrolyte will cause more transition metal ions to dissolve at the positive electrode, and these dissolved transition metal ions will be reduced at the negative electrode surface, thereby destroying the integrity, uniformity and stability of the SEI film on the negative electrode surface, which will cause the internal resistance of the lithium battery to increase, and the transitionally dissolved metal ions will also reduce the structural interface of the positive electrode material, which is not conducive to improving the cycle performance of the lithium battery.
[0013] Preferably, the CB value of the lithium battery is dd , the V ol satisfy
[0014] Preferably, the CB value of the lithium battery is in the range of 1.1-1.19.
[0015] Preferably, the CB value of the lithium battery is in the range of 1.11-1.17.
[0016] By adjusting the CB value of the lithium battery to meet the above range, the problem of electrolyte decomposition in the lithium battery can be avoided, which helps to improve the cycle performance of the lithium battery. When the CB value is high, the ratio between the lithium insertion capacity of the negative electrode and the lithium removal capacity of the positive electrode is large during the charge and discharge process of the lithium battery, which will cause the negative electrode to over-insert lithium during the charging process, which will not only consume a large amount of electrolyte, but also reduce the ion conduction efficiency of the electrolyte, resulting in excessive temperature rise inside the battery under high voltage, which will be detrimental to the improvement of the cycle performance and safety performance of the lithium battery; when the CB value is too low, the lithium ion insertion and extraction speed of the negative electrode is fast, which will cause the lithium salt in the electrolyte to be consumed faster. Since lithium salt is the main source of lithium ions in the electrolyte, the rapid consumption of lithium salt will cause the conductivity of the electrolyte to decrease, which will lead to a shortened cycle life of the lithium battery, a narrower operating temperature range, and even an increase in the safety risk of the battery.
[0017] Preferably, the weight percentage of the additive in each hundred parts of the electrolyte is A dd The value range is 3-5.2 parts.
[0018] Preferably, the weight percentage of the additive in each hundred parts of the electrolyte is A dd The value range is 3.3-4.7 parts.
[0019] By adjusting the proportion of additives in the electrolyte A dd Meeting the above range can avoid the destruction and recombination of the SEI film of the lithium battery caused by the dissolution of transition metal ions, which helps to improve the cycle performance of the lithium battery. dd If A is too high, it will hinder the formation of SEI film, resulting in poor stability of the final SEI film, which is not conducive to improving the cycle performance of lithium batteries. dd If it is too low, the SEI film generated at the negative electrode will be incomplete or of poor quality. The incomplete SEI film will hinder the transmission of lithium ions inside the battery, increase the internal resistance of the battery, reduce the discharge capacity and charging efficiency of the battery, and the incomplete SEI film cannot effectively protect the electrode material, which will lead to a significant decrease in the cycle performance of the lithium battery.
[0020] Preferably, the charging cut-off voltage V ol The value range is 4.2-4.3V.
[0021] Preferably, the charging cut-off voltage V ol The value range is 4.21-4.28V.
[0022] By controlling the charging cut-off voltage of the lithium battery to meet the above range, the capacity of the electrode material can be fully utilized, so that the energy density of the lithium battery can be maintained at a high level. In addition, the charging cut-off voltage is related to the CB value of the lithium battery and the proportion of the additive in the electrolyte.dd The combination will not cause the electrolyte to be oxidized and decomposed, nor will the transition metal ions be reduced at the negative electrode, thus avoiding the destruction and reorganization of the SEI film, allowing the lithium battery to have both high energy density and excellent cycle performance.
[0023] Preferably, the negative electrode film-forming additive includes at least one of vinylene carbonate VC, fluoroethylene carbonate FEC, and vinyl ethylene carbonate VEC; the positive electrode complexing additive includes at least one of trimethylsilyl phosphate TMSP and succinonitrile SN; the positive electrode high-voltage resistant additive includes at least one of 1,3-propane sultone PS and lithium difluorooxalatoborate LiDFOB.
[0024] Preferably, the lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; and the concentration of the lithium salt in the electrolyte is 0.85-1.5 mol / L.
[0025] Preferably, the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
[0026] Preferably, the solvent comprises cyclic carbonate and chain carbonate; the mass proportion of the solvent in the electrolyte is 80%-90%.
[0027] Preferably, the volume ratio of the cyclic carbonate to the linear carbonate is 3-4.5:5.5-7.
[0028] Preferably, the cyclic carbonate includes at least one of ethylene carbonate EC and propylene carbonate PC; the chain carbonate includes at least one of ethyl methyl carbonate EMC, diethyl carbonate DEC and dimethyl carbonate DMC.
[0029] Preferably, it also includes a positive electrode sheet and a negative electrode sheet; the compaction density of the positive electrode sheet is 2.0-2.6 g / cm 3 , and / or, the single-sided surface density of the positive electrode sheet is 200-260g / m 2 .
[0030] Preferably, the compaction density of the positive electrode sheet is 2.1-2.5 g / cm 3 , and / or, the single-sided surface density of the positive electrode sheet is 210-250g / m 2 .
[0031] Preferably, the compaction density of the negative electrode sheet is 1.55-1.75 g / cm 3 , and / or, the single-sided surface density of the negative electrode sheet is 80-110 g / m 2 .
[0032] Preferably, the filling coefficient of the lithium battery is 2.3-3.8 g / Ah.
[0033] The filling coefficient is the ratio of the electrolyte consumption of a lithium battery to the battery's own capacity under normal use.
[0034] By controlling the injection coefficient of the lithium battery to meet the above range, on the one hand, the electrolyte can be adjusted to produce a good wetting effect on the positive and negative electrode sheets, thereby significantly improving the capacity of the positive and negative electrode active materials and reducing the impedance of the positive and negative electrode sheets, which is not only beneficial to the energy density of the lithium battery, but also beneficial to improving the cycle performance of the lithium battery; on the other hand, the size of the secondary battery gas storage space can be adjusted, thereby reducing the swelling of the lithium battery during the cycle process, which helps to further improve the cycle performance of the lithium battery. DETAILED DESCRIPTION
[0035] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0037] Unless otherwise indicated, all numerical values expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.
[0038] As used herein, "and / or" means one or all of the mentioned elements.
[0039] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.
[0040] All percentages in this application are by weight unless otherwise stated.
[0041] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.
[0042] Example 1
[0043] 1. Preparation of electrolyte
[0044] The electrolyte includes a solvent, a lithium salt and an additive.
[0045] The lithium salt is composed of LiFSI and LiPF6 (mass ratio is 1:1), and the lithium salt concentration in the electrolyte is 1.1 mol / L;
[0046] (ethylene carbonate EC) and chain carbonate (ethyl methyl carbonate EMC), the mass ratio of the solvent in the electrolyte is 85%, of which the volume ratio of cyclic carbonate and chain carbonate is 4:6;
[0047] The additives are composed of vinylene carbonate VC, fluoroethylene carbonate FEC, succinonitrile SN, and lithium difluorooxalate borate LiDFOB, and the weight proportion of the additives in every hundred parts of the electrolyte is 3.
[0048] 2. Preparation of positive electrode
[0049] The positive electrode material (lithium manganese iron phosphate), conductive agent acetylene black, and binder PVDF were mixed in a mass ratio of 96:2:2, and the solvent NMP was added. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on both surfaces of the positive electrode current collector aluminum foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 220g / m 2 , compacted density is 2.4g / cm 3 The positive electrode.
[0050] 3. Negative electrode preparation
[0051] The negative electrode material (graphite), conductive agent acetylene black, and binder CMC were mixed in a mass ratio of 97:1.5:1.5, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on both surfaces of the negative electrode current collector copper foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 93.06 g / m 2 , compacted density is 1.6g / cm 3 The negative electrode.
[0052] 4. Lithium battery preparation
[0053] A stacking machine is used to stack the positive electrode sheet, isolation film, and negative electrode sheet in order, wherein the isolation film is a polyethylene film, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role. After stacking, the battery cell is assembled into an aluminum-plastic bag, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery with an injection coefficient of 3.5, a charging cut-off voltage of 4.2V, and a CB value of 1.1 is obtained.
[0054] Example 2
[0055] 1. Preparation of electrolyte
[0056] The electrolyte includes a solvent, a lithium salt and an additive.
[0057] The lithium salt is composed of LiFSI and LiPF6 (mass ratio is 1:1), and the lithium salt concentration in the electrolyte is 0.85 mol / L;
[0058] The solvent is composed of cyclic carbonate (ethylene carbonate EC) and chain carbonate (dimethyl carbonate DMC), and the mass proportion of the solvent in the electrolyte is 80%, wherein the volume ratio of the cyclic carbonate to the chain carbonate is 3:5.5;
[0059] The additives are composed of vinylene carbonate VC, fluoroethylene carbonate FEC, succinonitrile SN, and lithium difluorooxalate borate LiDFOB, and the weight proportion of the additives in every hundred parts of the electrolyte is 3.6.
[0060] 2. Preparation of positive electrode
[0061] The positive electrode material (lithium manganese iron phosphate), conductive agent acetylene black, and binder PVDF were mixed in a mass ratio of 96:2:2, and the solvent NMP was added. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on both surfaces of the positive electrode current collector aluminum foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 220g / m 2 , compacted density is 2.4g / cm 3 The positive electrode.
[0062] 3. Negative electrode preparation
[0063] The negative electrode material (graphite), conductive agent acetylene black, and binder CMC were mixed in a mass ratio of 97:1.5:1.5, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on both surfaces of the negative electrode current collector copper foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 95.6 g / m 2 , compacted density is 1.6g / cm 3 The negative electrode.
[0064] 4. Lithium battery preparation
[0065] A stacking machine is used to stack the positive electrode sheet, isolation film, and negative electrode sheet in order, wherein the isolation film is a polyethylene film, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role. After stacking, the battery cell is assembled into an aluminum-plastic bag, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery with an injection coefficient of 3.5, a charging cut-off voltage of 4.23V, and a CB value of 1.13 is obtained.
[0066] Example 3
[0067] 1. Preparation of electrolyte
[0068] The electrolyte includes a solvent, a lithium salt and an additive.
[0069] The lithium salt is composed of LiFSI and LiPF6 (mass ratio is 1:1), and the lithium salt concentration in the electrolyte is 1.3 mol / L;
[0070] The solvent is composed of cyclic carbonate (ethylene carbonate EC and propylene carbonate PC in a volume ratio of 1:1) and chain carbonate (ethyl methyl carbonate EMC). The mass ratio of the solvent in the electrolyte is 90%, of which the volume ratio of the cyclic carbonate to the chain carbonate is 4.5:7;
[0071] The additives are composed of vinylene carbonate VC, fluoroethylene carbonate FEC, trimethylsilyl phosphate TMSP and 1,3-propane sultone PS, and the weight proportion of the additives in every hundred parts of the electrolyte is 4.4.
[0072] 2. Preparation of positive electrode
[0073] The positive electrode material (lithium manganese iron phosphate), conductive agent acetylene black, and binder PVDF were mixed in a mass ratio of 96:2:2, and the solvent NMP was added. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on both surfaces of the positive electrode current collector aluminum foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 220g / m 2 , compacted density is 2.4g / cm 3 The positive electrode.
[0074] 3. Negative electrode preparation
[0075] The negative electrode material (graphite), conductive agent acetylene black, and binder CMC were mixed in a mass ratio of 97:1.5:1.5, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on both surfaces of the negative electrode current collector copper foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 97.3 g / m 2, compacted density is 1.6g / cm 3 The negative electrode.
[0076] 4. Lithium battery preparation
[0077] A stacking machine is used to stack the positive electrode sheet, isolation film, and negative electrode sheet in order, wherein the isolation film is a polyethylene film, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role. After stacking, the battery cell is assembled into an aluminum-plastic bag, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery with an injection coefficient of 3.5, a charging cut-off voltage of 4.27V, and a CB value of 1.15 is obtained.
[0078] Example 4
[0079] 1. Preparation of electrolyte
[0080] The electrolyte includes a solvent, a lithium salt and an additive.
[0081] The lithium salt is composed of LiFSI and LiPF6 (mass ratio is 1:1), and the lithium salt concentration in the electrolyte is 1.1 mol / L; the solvent is composed of cyclic carbonate (ethylene carbonate EC and propylene carbonate PC in a volume ratio of 2:1) and chain carbonate (diethyl carbonate DEC). The mass ratio of the solvent in the electrolyte is 83%, of which the volume ratio of cyclic carbonate to chain carbonate is 3.5:6;
[0082] The additives are composed of vinylene carbonate VC, vinyl ethylene carbonate VEC, succinonitrile SN, and lithium difluorooxalate borate LiDFOB, and the weight proportion of the additives in every hundred parts of the electrolyte is 5.2.
[0083] 2. Preparation of positive electrode
[0084] The positive electrode material (lithium manganese iron phosphate), conductive agent acetylene black, and binder PVDF were mixed in a mass ratio of 96:2:2, and the solvent NMP was added. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on both surfaces of the positive electrode current collector aluminum foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 220g / m 2 , compacted density is 2.4g / cm 3 The positive electrode.
[0085] 3. Negative electrode preparation
[0086] The negative electrode material (graphite), conductive agent acetylene black, and binder CMC were mixed in a mass ratio of 97:1.5:1.5, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on both surfaces of the negative electrode current collector copper foil, and after double-layer coating, it was dried at room temperature and then transferred to an oven for further drying, and then cold pressed and cut to obtain a surface density of 100.6 g / m 2 , compacted density is 1.6g / cm 3 The negative electrode.
[0087] 4. Lithium battery preparation
[0088] A stacking machine is used to stack the positive electrode sheet, isolation film, and negative electrode sheet in order, wherein the isolation film is a polyethylene film, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role. After stacking, the battery cell is assembled into an aluminum-plastic bag, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery with an injection coefficient of 3.5, a charging cut-off voltage of 4.3V, and a CB value of 1.19 is obtained.
[0089] Example 5
[0090] The difference between this embodiment and embodiment 1 is that the additives in the electrolyte include vinylene carbonate VC, fluoroethylene carbonate FEC, vinyl ethylene carbonate VEC, trimethylsilyl phosphate TMSP, succinonitrile SN, 1,3-propane sultone PS, and lithium difluorooxalatoborate LiDFOB; the remaining steps and parameter settings are consistent with those in embodiment 1.
[0091] Example 6
[0092] The difference between this embodiment and embodiment 1 is that the CB value of the lithium battery is 1.05, the charge cut-off voltage is 4.35V, and the weight parts of the additive per hundred parts of the electrolyte is 2.98; the other steps and parameter settings are consistent with those in embodiment 1.
[0093] Example 7
[0094] The difference between this embodiment and embodiment 1 is that the CB value of the lithium battery is 1.25, the charge cut-off voltage is 4.15V, and the weight parts of the additive per hundred parts of the electrolyte is 5; the other steps and parameter settings are consistent with those in embodiment 1.
[0095] Example 8
[0096] The difference between this embodiment and embodiment 1 is that the liquid filling coefficient of the lithium battery is 2.0; the remaining steps and parameter settings are consistent with those of embodiment 1.
[0097] Example 9
[0098] The difference between this embodiment and embodiment 1 is that the liquid filling coefficient of the lithium battery is 4.0; the remaining steps and parameter settings are consistent with those of embodiment 1.
[0099] Comparative Example 1
[0100] The difference between this embodiment and the embodiment is that the weight percentage of the additive in every hundred parts of the electrolyte is 5.25. The remaining steps and parameter settings are consistent with those in Example 1.
[0101] Comparative Example 2
[0102] The difference between this embodiment and the embodiment is that the charging cut-off voltage Vol of the lithium battery is 4.34V. The remaining steps and parameter settings are consistent with those in Example 1.
[0103] Comparative Example 3
[0104] The difference between this embodiment and embodiment 1 is that the additive does not contain a negative electrode film-forming additive, and an equal weight of a positive electrode complexing additive is used to replace the negative electrode film-forming additive in embodiment 1; the remaining steps and parameter settings are consistent with embodiment 1.
[0105] Comparative Example 4
[0106] The difference between this embodiment and embodiment 1 is that the additive does not contain a positive electrode complexing additive, and an equal weight of a positive electrode high-voltage resistant additive is used to replace the positive electrode complexing additive in embodiment 1; the remaining steps and parameter settings are consistent with embodiment 1.
[0107] Comparative Example 5
[0108] The difference between this embodiment and embodiment 1 is that the additive does not contain the positive electrode high voltage resistant additive, and the negative electrode film-forming additive of equal weight is used to replace the positive electrode high voltage resistant additive in embodiment 1; the remaining steps and parameter settings are consistent with embodiment 1.
[0109] Test Method
[0110] 1. Lithium battery energy density test
[0111] The energy density test was performed on the lithium batteries in the above embodiments and comparative examples. The specific test steps were as follows: weigh the weight of the battery to be tested, recorded as m; place the battery in a fixture, apply a force of 3000N, charge the single battery to 4.3V at a constant current of 0.33C, leave it for 30min, discharge it to 2.5V at a constant current of 0.33C, leave it for 30min, charge and discharge it continuously for 3 times, calculate the third discharge capacity (in Ah) and energy E (take the average value of three cells), discharge energy density: E / m (in Wh / kg).
[0112] 2. Lithium battery cycle performance test
[0113] The lithium batteries in the above embodiments and comparative examples were tested for cycle performance. The lithium batteries were fully charged and discharged at 25°C. The specific test steps were: leave for 30 minutes; charge with constant current and constant voltage, with a current of 0.33C, a constant voltage of 4.2V, and a cut-off current of 0.05C (C is the battery design capacity), and cycle three times, with the capacity of the last cycle being Q rated capacity. Leave for 1 hour, charge with constant current and constant voltage, with a current of 1Q, a constant voltage of 4.2V, and a cut-off current of 0.05Q; leave for 1 hour; discharge with constant current, with a current of 1Q, cycle 2000 times, and record the cycle capacity retention rate of the lithium battery.
[0114] 3. Negative electrode ICP test
[0115] The contents of Mn and Fe in the negative electrode materials of the negative electrode sheets of the lithium batteries after the cycle treatment in the above-mentioned embodiments and comparative examples were measured by ICP.
[0116] Table 1
[0117]
[0118] Combining Examples 1-5, Comparative Examples 1-2 and Table 1, it can be seen that the present invention satisfies the following conditions by controlling the weight of the additive Add in every hundred parts of the electrolyte, the charging cut-off voltage Vol of the lithium battery and the CB value of the lithium battery: It can reduce the deposition of transition metal ions at the negative electrode and ensure the complexation of transition metal ions at the positive electrode as much as possible, thereby improving the stability of the electrolyte and the stability of the SEI film at the negative electrode surface, thereby ensuring the energy density of the lithium battery and having good cycle performance.
[0119] In Comparative Example 1, the weight proportion of additives in every hundred parts of electrolyte is excessive. Except for the additive amount required for the film formation of the positive and negative electrodes themselves, the remaining additives produce side reactions in the electrolyte, which will increase the impedance of the lithium battery and reduce the cycle performance of the lithium battery. However, the excessive additives also play a certain protective role on the surfaces of the positive and negative electrodes, so the deposition of transition metal ions at the negative electrode is not significantly improved.
[0120] In Comparative Example 2, the charging cut-off voltage of the lithium battery increases, and the weight percentage of the additives per hundred parts of the electrolyte remains unchanged. During the voltage increase, the CEI film and the SEI film are destroyed, and no additional additives are involved in the film formation in time, so the dissolution of the transition metal cannot be suppressed, and the transition metal ion deposition phenomenon at the negative electrode is significant; when the additives in the electrolyte are exhausted, the solvent in the electrolyte also begins to decompose, which will further deteriorate the cycle performance of the lithium battery.
[0121] In comparative examples 3-5, when any one of the negative electrode film-forming additive, the positive electrode complexing additive, and the positive electrode high-voltage resistant additive is missing, it will be unfavorable for the coordination between the additives to maintain the stability of the electrolyte, especially the lack of the positive electrode high-voltage resistant additive, which will significantly increase the deposition of transition metal ions at the negative electrode, and the cycle performance of the lithium battery will also be significantly reduced; and when the negative electrode film-forming agent or the positive electrode complexing agent is missing, although it can alleviate the dissolution of the positive electrode transition metal ions to a certain extent to reduce the deposition of transition metal ions at the negative electrode, the protective effect of the additive on the positive and negative electrodes is greatly weakened at this time, and the cycle performance of the lithium battery is seriously deteriorated.
[0122] Combining Examples 1, 6-7 and Table 1, it can be seen that when the CB value is too small, the charge cut-off voltage Vol is too large and Add is too small, although the relationship between the three still satisfies However, if Add is too small, the SEI film generated at the negative electrode will be incomplete or of poor quality, and the CB value and Vol will not work well together, resulting in a decrease in the stability of the electrolyte, which is not conducive to adjusting the cycle performance of the lithium battery. The phenomenon of transition metal ion deposition at the negative electrode is more significant than in Example 1; when the CB value is too large and the charge cut-off voltage Vol is too small, the energy density of the lithium battery decreases slightly, and excessive lithium insertion will occur at the negative electrode during the charging process, which will not only consume a large amount of electrolyte, but also reduce the ion conduction efficiency of the electrolyte, which will be detrimental to the improvement of the cycle performance of the lithium battery.
[0123] Combining Examples 1, 8-9 and Table 1, it can be seen that when the injection coefficient is too small, it helps to increase the energy density of the lithium battery, but the long cycle process is usually accompanied by the continuous consumption of the electrolyte. If the injection coefficient is too low, the electrolyte will be insufficient to maintain a long cycle, thereby deteriorating the cycle performance of the lithium battery; when the injection coefficient is too high, the energy density of the lithium battery is reduced, and there are many side reactions in the electrolyte, which will increase the impedance of the lithium battery and deteriorate the cycle performance.
[0124] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.
Claims
1. A lithium ion battery, characterized in that: The electrolyte includes a solvent, a lithium salt and an additive, and the weight of the additive per hundred parts of the electrolyte is recorded as A. dd , A dd The unit is part, and the charging cut-off voltage of the lithium battery is recorded as V ol , V ol The unit is V; The CB value of the lithium battery is related to the A dd , the V ol satisfy The CB value of the lithium battery is a dimensionless value; Among them, the additives include negative electrode film-forming additives, positive electrode complexing additives, and positive electrode high-voltage resistant additives.
2. The lithium-ion battery according to claim 1, characterized in that: The CB value of the lithium battery is related to the A dd , the V ol satisfy 3. The lithium ion battery according to claim 1 or 2, characterized in that: The CB value of the lithium battery ranges from 1.1 to 1.
19.
4. The lithium ion battery according to claim 1 or 2, characterized in that: The weight percentage of the additive in the electrolyte is A dd The value range is 3-5.2 parts.
5. The lithium ion battery according to claim 1 or 2, characterized in that: The charging cut-off voltage V of the lithium battery ol The value range is 4.2-4.3V.
6. The lithium-ion battery according to claim 1, characterized in that: The negative electrode film-forming additive includes at least one of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate; The positive electrode complexing additive includes at least one of trimethylsilyl phosphate and succinonitrile; The positive electrode high voltage resistant additive includes at least one of 1,3-propane sultone and lithium bifluorooxalatoborate.
7. The lithium-ion battery according to claim 1, characterized in that: The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; and the concentration of the lithium salt in the electrolyte is 0.8-1.5 mol / L.
8. The lithium-ion battery according to claim 1, characterized in that: It also includes a positive electrode sheet and a negative electrode sheet; the compaction density of the positive electrode sheet is 2.0-2.6g / cm 3 , and / or, the single-sided surface density of the positive electrode sheet is 200-260g / m 2 .
9. The lithium-ion battery according to claim 8, characterized in that: The compaction density of the negative electrode sheet is 1.55-1.75 g / cm 3 , and / or, the single-sided surface density of the negative electrode sheet is 80-110 g / m 2 .
10. The lithium-ion battery according to claim 1, characterized in that: The liquid injection coefficient of the lithium battery is 2.3-3.8 g / Ah.
Citation Information
Patent Citations
High-voltage lithium ion battery and electrolyte thereof
CN104269577A
Secondary battery and device
CN116417677A
Lithium ion battery
CN117219856A
Secondary battery and electric equipment
CN117977001A
Lithium ion battery and electric device
CN118402106A
Cited By
Lithium-ion battery
EP4783289A1
Lithium-ion battery
WO2026123443A1